Assessment of Rhodolith Diversity in the Northwestern Gulf of Mexico Including the Description of Sporolithon gracile sp. nov. (Sporolithales, Rhodophyta), and Three New Species of Roseolithon (Hapalidiales, Rhodophyta) - Richards, Joseph; Kittle, Ronald P.; Schmidt, William E.; Sauvage, Thomas; Gurgel, Carlos F. D.; Gabriel, Daniela; Fredericq, Suzanne (Frontiers in Marine Science, 2022)
In the past, non-geniculate coralline algae in the northwestern Gulf of Mexico have been identified based primarily on comparative morpho-anatomy. Recent studies employing DNA sequencing techniques combined with morpho-anatomical studies using SEM have revealed a wealth of previously undocumented diversity of rhodolith-forming non-geniculate coralline algae in the Corallinales, Hapalidiales and Sporolithales from mesophotic hard bank communities at 45-90 meters depth. Although many advances in the last decade have been made in clarifying species names and describing new species of corallines from offshore Louisiana and Texas, total diversity estimates are still incomplete and many species remain to be described. Collections from offshore Louisiana at Parker Bank in the newly expanded Flower Garden Banks National Marine Sanctuary yielded thin, finely branched rhodoliths. DNA sequence analyses of plastid-encoded psbA and rbcL loci, and nuclear-encoded LSU rDNA of these rhodolith-forming specimens revealed that some belong to an unnamed species of Sporolithon (Sporolithales) that we herein newly describe. Additionally, comparative DNA sequence analyses of rhodolith collections from Ewing Bank and other hard banks offshore Louisiana were conducted to assess rhodolith diversity in these mesophotic communities. The results revealed new reports of taxa for the region, including new rhodolith-forming species of Roseolithon (Hapalidiales) to be described herein as well. Our new biodiversity findings will be compared with historical studies from the NW Gulf of Mexico.